Photo-production of psi(2S) mesons at HERA - Adloff, C; Aid, S; Anderson, M; Andreev, V; Andrieu, B; Arkadov, V; Arndt, C; Ayyaz, I; Babaev, A; Bahr, J; Ban, J; Baranov, P; et al. (1998)
Quasi-elastic (z > 0.95) photo-production of ψ(2S) mesons has been observed at HERA for photon-proton centre-of-mass energies in the range 40 to 160 GeV. The ψ(2S) mesons were identified through their decays to ℓ+ℓ- and to J/ψπ+π-, where the J/ψ subsequently decays to ℓ+ℓ-, the lepton ℓ being either a muon or an electron. The cross-section for quasi-elastic photoproduction was measured to be (18.0 ± 2.8(stat) ± 3.0(syst)) nb at a photon-proton centre-of-mass energy of 80 GeV. The ratio of the ψ(2S) to J/ψ quasi-elastic cross-sections is (0.150 ± 0.027(stat) + 0.022(syst)). © 1998 Elsevier Science B.V.